Imam Ali (PBUH) in the thought of Al-nadham Ibrahim bin Sayyar Al-Mu'tazili (d. 231 AH / 846 AD) - Natish, Prof. Dr. Kazem Abd; Kamel, Akram Hatem (Thi Qar Arts Journal, 2023)
The research aims to study the doctrinal tendencies of the Nizam's thought, which were a cause of prejudice against him by some of his fellow Mu'tazilites and some other sects. For Imam Ali bin Abi Talib (PBUH)? And based on the attempt to answer this question, the research was built on three axes, according to what we received from the quotes about the regime in this regard. (PBUH) For the hadith, the third axis was entitled The Regime’s Position on Imam Ali (PBUH) and those who disobeyed his caliphate.